HOW A SENTENCE IS CONSTRUCTED: A SYNTACTIC ANALYSIS ON ESL’S WRITING TEXT - Hijjatul Qamariah (Getsempena English Education Journal, 2015)
Constructing a sentence grammatically and syntactically correct has become a cliché but crucial problem for English as Second Language (ESL) learners. The problem is also faced by ESL teachers, significantly in correcting the students’ papers and finding the solutions for this problem. The pattern of the sentences then should be analyzed in order to find a predominant pattern normally constructed by the learners. This article tries to look and explore that point by analyzing the syntactic and grammar aspects of the sentences written by ESL Learners. Two samples of ESL learners’ writing paper are used as documents to be analyzed. The samples are taken from two different level of English proficiency called S2 and S4. The analysis is divided into two parts. Part one is the quantitative analysis which reveals the calculation of the analysis on several points such as, types of clause, sub clauses, tenses, aspects, verbs, objects, references, and antecedent of S2 and S4 writing text and it illustrates how many of each component appears in both learners’ texts. Those findings are presented in tables and they are attached in appendices. Moreover, part two, qualitatively the result of quantitative method is explained more than only numbers, by giving more details on the pattern of the sentences written by two learners and also to draw a prediction made before. Thus, it is found that the learners have problems in constructing complete sentences, such as lack of subject and verb and subject-verb agreement errors. S2 learner tends to use more personal pronouns comparing to S4 learners, it is assumed because of his lack of syntax repertoire in constructing more complex and compound sentences. The progress of syntactic system of S2 is showed by correctly used of tense, reference, and proper subject. S4 writing text is categorized as a well developed of syntactic system. The confident use of different sentence structure, vary of vocabulary and has a good persuasive sentences reflect on his writing. The sentences written by S2 and S4 learner predominantly have SVO (Np +(aux)+ Vp) pattern and mix with the compound and complex sentences, where clause sometimes can be objects and complement. For instance, I am a duck who traveled in the sea (S (Np+Vp)+S-bar) and I’m not a callous person but I’m in favour that he should have been left to die on Mount Everest for these following reasons (s(Np+Vp)CC+s(Np+Vp). This study’s findings would benefit the writer, especially for teachers, they should consider the learners’ level, and what kind of instruction should be good to apply in order to maximize learners’ comprehension.